Chemical constituents from the leaves of Achornea rugosa (Lour.) Müll. Arg. (Euphorbiaceae) - Huyen, Pham Van; Hien, Nguyen Thi Thu; Duyen, Nguyen Huu Huong; Thuan, Nguyen Thi Dieu; Phan, Nguyen Huu Toan (Vietnam Journal of Science and Technology, 2022)
Alchornea is a genus of plants in the family Euphorbiaceae. It is widely distributed in tropical and subtropical regions of Africa, South Asia, Australia, and Latin America. Many species of the genus Alchornea have been used in traditional medicine in some countries around the world. Therefore, there have been many studies focusing on the chemical composition and biological activities of some species of the genus Alchornea. In the research project on the chemical composition of 4 species of Alchornea distributed in Viet Nam, we have reported compounds isolated from 3 species A. tiliaefolia, A. annamatica, and A. trewioides. Alchornea rugosa grows wild throughout Viet Nam and has been used in traditional medicine, but little is known about its chemical composition. From the leaves of species A. rugosa collected in Me Linh district, Ha Noi city, Viet Nam, five compounds including 3β-friedelanol (1), friedelan-3-one (2), methyl syringate (3), isovitexin (4), and rhoifolin (5) has been isolated from the methanol extract from its leaves by different chromatographic techniques. Their chemical structures were determined based on 1D and 2D NMR spectroscopy and mass spectrometry analysis and comparison with reference material. This is the first report on the isolation of these compounds from A. rugosa.